A felicidade na perspectiva de idosos institucionalizados - Kaczalla, Fernanda Kesties (2017)
The theme of happiness often appears in various places and sectors of human knowledge emphasizing its importance. In contemporary society, it has been common to meet people by creating and recreating situations that favor social and personal well-being, revealing in humanity an immense desire to be happy, to meet and walk with happiness. This study aimed to know the conception of happiness from the perspective of institutionalized elders. To achieve this objective, a descriptive qualitative approach developed, with the participation of nineteen individuals aged older residing in long-term institutions located in the northern region of Rio Grande do Sul. The inclusion criteria were age Equal or superior to 60 years, of both sexes, in conditions of communication and preserved verbalization and obtaining minimum scores in the Mental State Mini Exam. The results indicate that happiness in old age emphasizes health status and conditioned to multiple dimensions: relational, which encompasses family ties and friendships; the occupational that refers to activities and occupations precedes institutiona lization. The physical dimension, in which functionality gains prominence as determinant of happiness. In addition, the material dimension, which directs to material and financial resources, without which there is evidence of impairment in living conditions. In addition, repercussions on the perception of happiness. Considering the results of this study, it concluded that, for the institutionalized elderly, happiness tends to related to the four different dimensions. Being relevant to elucidate the relationship between happiness and health conditions, because happiness and good -Assessment of individuals and populations is the ultimate goal, because it is human nature, according to its context and situation, the pursuit of happiness as the fulfillment of each person.